Documenting Ourselves : Film, Video, and Culture - Sherman, Sharon R. (Book collections on Project MUSE., 1998)
Since Robert Flaherty's landmark film Nanook of the North (1922) arguments have raged over whether or not film records of people and traditions can ever be ""authentic."" And yet never before has a single volume combined documentary, ethnographic, and folkloristic filmmaking to explore this controversy. What happens when we turn the camera on ourselves? This question has long plagued documentary filmmakers concerned with issues of reflexivity, subject participation, and self-consciousness. Documenting Ourselves includes interviews with filmmakers Les Blank, Pat Ferrero, Jorge Preloran, Bill F.